CAUSAL FACTORS AND IMPACTS OF SEXUAL VIOLENCE AGAINST CHILDREN, AND THE URGENCY OF LAW NUMBER 12 OF 2022 (TPKS LAW) FOR VICTIMS - Aulia Febriliana Basyuni; Iwan Darmawan; Asmak Ul Hosnah (Awang Long Law Review, 2026)
Sexual violence is a violation of the law involving sexual acts without the victim's consent, whether physical or non-physical, including harassment, sexual exploitation, coercion, and electronic-based violence. Regulations regarding this criminal act are stipulated in Law Number 12 of 2022 concerning Sexual Violence Crimes. Article 4 paragraph (2) states that non-physical actions such as gestures, writing, or words related to a person's body parts or sexual desires can be subject to criminal sanctions as a form of non-physical sexual harassment. This research aims to provide a comprehensive overview of sexual violence crimes and formulate recommendations to promote the optimal implementation and enforcement of the law. This research uses a normative legal method by examining relevant laws and regulations and literature. The research findings indicate that sexual violence is influenced by various complex factors, including gender inequality, patriarchal social norms, a lack of education about sexuality and the law, and a weak law enforcement and victim protection system. This finding confirms the need to strengthen regulations, public education, and protection mechanisms to reduce the number of sexual violence cases and ensure justice for victims.